Assessment of Beach Abration Vulnerability Levels and Directions for Space Utilization in Central Pariaman District Pariaman City - Haryani, Haryani; Aditya, Ezra (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Haryani (2012, 2018) in the coastal area of ​​West Sumatra Province from 2003-2016 there has been a disaster of coastal abrasion and accretion at 32 points. During the 13 years, there was beach abrasion covering an area of ​​732.69 ha and coastal accretion covering an area of ​​55.4 ha. Coastal abrasion disaster causes a significant reduction in coastal land, namely an average of 56.3 ha / year, while the addition of coastal / coastal land is only 4.26 ha / year.This study aims to find the level of vulnerability of coastal abrasion in Central Pariaman District, Pariaman City. Physical, social, economic, and environmental parameters were analyzed using the scoring method according to Perka BNPB No. 2 of 2012. The results showed that the index of coastal abrasion vulnerability in Karan Aur, Lohong and Pasir villages had a moderate index, while Pauh Barat village had a high vulnerability index. Coastal abrasion mitigation is carried out by means of active mitigation and passive mitigation. Passive mitigation includes directional use of space where in the zone of 100 - 150 m from the highest tide and the growing beach is directed as a conservation area by planting mangroves and Pinago trees and agro-tourism (limited tourism). The cultivation zone is a zone that is located> 150 m from the highest tide inland, which is a safe zone for coastal abrasion for settlements and trade.